2017
DOI: 10.3390/ijms18071476
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination in Periodontal Disease: A Review

Abstract: Periodontal disease (periodontitis) is a chronic inflammatory condition initiated by microbial infection that leads to gingival tissue destruction and alveolar bone resorption. The periodontal tissue’s response to dental plaque is characterized by the accumulation of polymorphonuclear leukocytes, macrophages, and lymphocytes, all of which release inflammatory mediators and cytokines to orchestrate the immunopathogenesis of periodontal disease. Ubiquitination is achieved by a mechanism that involves a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 73 publications
(93 reference statements)
0
27
0
Order By: Relevance
“…The possible mechanism of association between rs10043775 and changes in the subgingival microbiological pattern is completely uncertain, since there is no direct evidence of FBXO38 association with host response. However, due its putative role in the ubiquitination process, which in turn has been implicated in the immune response, it could exert some impact over periodontal microbiota via this pathway [ 89 ]. However, it is possible that a yet unknown mechanism is responsible for the differential susceptibility to periodontitis demonstrated by our sample, or alternatively that rs10043775 is in linkage disequilibrium with another variant that is truly responsible for the changes in the subgingival microbiological pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of association between rs10043775 and changes in the subgingival microbiological pattern is completely uncertain, since there is no direct evidence of FBXO38 association with host response. However, due its putative role in the ubiquitination process, which in turn has been implicated in the immune response, it could exert some impact over periodontal microbiota via this pathway [ 89 ]. However, it is possible that a yet unknown mechanism is responsible for the differential susceptibility to periodontitis demonstrated by our sample, or alternatively that rs10043775 is in linkage disequilibrium with another variant that is truly responsible for the changes in the subgingival microbiological pattern.…”
Section: Discussionmentioning
confidence: 99%
“…They are important regulators of T‐cell and innate immune function through activation of NF‐κB. Ubiquination has been recently implicated in periodontitis . P. gingivalis produces a ubiquitin‐ligase Smurf‐1 dependent degradation of MyD88, an upstream regulator NF‐κB in neutrophils, and results in elevated type‐1 interferon .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Periodontal diseases (PDs) include a group of inflammatory diseases characterized by periodontium hard and soft tissues destruction leading to host immune response activation. 3 It has been reported that PDs as one of the two biggest threats to the oral health have a high prevalence in United States and they have been found in nearly half (45.9%) of the population aged 30 years and older. 4,5 Further, it has been revealed that PDs affect up to 15% of the population of childbearing age and some degrees of PDs can be seen in relatively high proportions of pregnant women.…”
Section: Mini Reviewmentioning
confidence: 99%